Epilepsy, epileptiform discharges and features of brain magnetic resonance imaging in merosin-deficient muscular dystrophy - A. V. Monakhova; E. D. Belousova; Z. K. Gorchkhanova (Эпилепсия и пароксизмальные состояния, 2025)
Background. Merosin-deficient muscular dystrophy (MDMD) is a neuromuscular disease resulting from the emergence of biallelic variants in the LAMA2 gene and manifested by progressive muscle weakness, diffuse hypotonia, impaired posture, contractures of large joints, and respiratory pathology. Epilepsy is a common symptom of MDMD. However, at the moment, the clinical course of epilepsy in MDMD remains understudied.Objective: To determine the features of epilepsy, electroencephalographic (EEG), radiological characteristics in MDMD patients, to identify a relation between brain pathological changes and the course of epilepsy, pathology on the EEG data and the location of nucleotide sequence variants within the LAMA2 gene.Material and methods. The study analyzed the EEG from 63 subjects with a genetically verified MDMD diagnosis. At the Veltishchev Research Clinical Institute of Pediatrics and Pediatric Surgery, an interictal EEG was carried out in 29 patients, the native data of an interictal EEG performed at the place of residence were collected and reanalyzed for 34 patients. Clinical and neurological statuses were assessed in all patients; 55 patients underwent brain magnetic resonance imaging (MRI).Results. Epilepsy was observed in 12 of 63 (19%) patients with MDMD and was characterized by a relatively late onset – 11.5 years of age. A predominantly focal seizure pattern was noted: 7 of 12 (58.4%) patients. The percentage of pharmacoresistance was comparable to epilepsy in general and amounted to 4 of 12 (33.3%) cases. Twelve of 51 (23.5%) subjects without epileptic seizures had EEG-verified epileptiform activity. Changes in brain MRI were represented by leukopathy, which was registered in all patients aged above 1 year old, as well as bilateral occipital pachygyria in 4 of 63 (6.3%) cases. In the presented group, no statistically significant relationship between disease form, EEG changes, central nervous system pathology and the presence of nucleotide sequence variants in the LG domain was found. The lack of correlation between such parameters may be due to a relatively small number of patients examined.Conclusion. Our study has advanced in understanding the course of epilepsy in MDMD. Given the presence of somatic complications masking epileptic seizures, it is necessary to be alert for epilepsy for timely diagnostics and care in this group of patients.